ROLE IN DEVELOPING THE CONCEPT MUHAMMAD NATSIR ISLAMIC EDUCATION IN INDONESIA 1932-1942 - Yulisniawati '; Marwoto Saiman Marwoto Saiman; Ridwan Melay Ridwan Melay (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Islamic education in Indonesia is education based on monotheism. Muhammad Natsir monotheism view that education should be given to children as early as possible while still young and easily cultivated, before preceded by the material, ideology and understanding of others. Indonesia has the world's treasures of Islamic education reformers were so many, the figures are very intense and pay great attention tehadap development and advancement of Islamic education. The purpose of this study was to determine History Education Muhammad Natsir, To know the concept of Islamic Education Muhammad Natsir, To know Muhammad Natsir Efforts in Developing Islamic Education Concepts Muhammad Natsir. This study uses historical method that will give a clear picture of the past in a systematic, objective to collect, evaluate and interpret the obtained materials that can be accounted for righteousness. Muhammad Natsir concept of Islamic education Universal, Integral and Harmony is the result of reflections Muhammad Natsir of Qur'an and Sunnah. Integrative education proposed by Muhammad Natsir based on monotheism, and aims to make man who serve Allah. Education concept Muhammad Natsir accompanied by his efforts in promoting Islamic education is seen in Mendirian Pendis, Establishing Institutions of Islamic Da'wah and Islamic Pioneering High School Establishment UII. The concept of Islamic Education Muhammad Natsir seen with the objective of Islamic Education, Islamic Education Platform, Urgency Islamic Education, Implementation of Islamic Education, Islamic Education materials and methods Islam.Pemikiran Education Muhammad Natsir on Islamic Education has been proven by many schools and universities High Islam and Islamic universities which have definite and clear curriculum.Key words: Islamic education Dutch era, Japan, and Islamic education M. Natsir